Aspek Perlindungan Hukum Nasabah dalam Sistem Pembayaran Internet - Budi Agus Riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2001)
The Problem of legal security and certaintyis a negative effect of e-commerce development. The efforts togive legal protection to customers canbe done by using The Most Characteristic Connection Theory. Indonesian contract law can only be applied if thesuppliers of internet payment service are in Indonesia. In spite of the fact that Indonesian authentication law has been unfamiliar with digital signatureas written evidence, the emerging controversy can be settled by using conventional ADR or on line ADR agency.